The Activities of the Koçuşağı (Koçan) Tribe in the Dersim Sanjak in the Last Period of the Ottoman Empire and the Koçuşağı Military Operation (1926) - Taş, Erhan (Fırat University, 2025)
The geographical conditions contributed to Dersim's isolation from the surrounding area. The lack of a significant population and income in the region meant that the administration remained indifferent to the area. In the mountainous parts of the Sanjak, where the central authority was ineffective, tribal life dominated. Tribal chiefs filled the power vacuum in their favor and used the tribes to their advantage. Tribal banditry emerged in the context of tribal structure and economic conditions and became an established custom over time. One of the important tribes living in the region is the Koçuşağı tribe. This tribe has become the center of law and order problems in the region as they constantly commit acts of banditry in addition to their high-handed behavior. From time to time, their banditry developed into rebellions in which many tribes participated. This thematic study, synthesized from archival documents, examines the general characteristics of the Koçuşağı tribe that lived in Sanjak Dersim, the acts of banditry and rebellion, the influence of the tribe on the formation of a negative perception of Sanjak Dersim, and the military operation organized against the tribe in 1926 during the Republic of Turkey and its results. In this way, an attempt was made to shed light on the Koçuşağı tribe, which has influenced the history of the region at the micro level, from various aspects.

Coğrafi şartlar Dersim sancağının çevreden yalıtılmasına zemin hazırlamıştır. Bölgenin önemli miktarda nüfus ve gelire sahip olmaması yönetimin bölgeye ilgisiz kalmasına sebep olmuştur. Merkezi otoritenin etkisiz kaldığı sancağın dağlık kesimlerinde aşiret yaşamı hâkim olmuştur. Aşiret reisleri otorite boşluğunu kendi lehine doldurarak, aşiretleri istedikleri yönde kullanmıştır. Aşiret yapısı ve ekonomik şartlarla bağlantılı olarak aşiret eşkıyalığı türemiş, bu durum zamanla yerleşik bir alışkanlığa dönüşmüştür. Bölgede yaşayan önemli aşiretlerden biri de Koçuşağı Aşireti’dir. Bu aşiret başına buyruk tavırlarının yanı sıra sürekli eşkıyalık eylemlerinde bulunarak bölgede asayiş sorunlarının merkezi haline gelmiştir. Eşkıyalık eylemleri zaman zaman birçok aşiretin katıldığı isyana evrilmiştir. Arşiv belgelerinin sentezine dayalı olarak hazırlanan bu tematik çalışmada, Dersim sancağında yaşayan Koçuşağı Aşireti’nin genel özellikleri, gerçekleştirdiği eşkıyalık ve isyan eylemleri, aşiretin Dersim sancağı hakkında olumsuz algının oluşması üzerindeki etkisi ve 1926 yılında Türkiye Cumhuriyeti Dönemi’nde aşirete yönelik düzenlenen askerî harekât ve sonuçları irdelenmiştir. Bu yolla bölge tarihi üzerinde mikro düzeyde bir etkiye sahip olan Koçuşağı Aşireti farklı yönleriyle ortaya konmaya çalışılmıştır.
Dersim Sancağında Yaşayan Koçuşağı (Koçan) Aşireti’nin Osmanlı Devleti’nin Son Dönemindeki Faaliyetleri Ve Koçuşağı Askerî Harekâtı (1926)
Keywords: History of The Republic of Turkiye; Türkiye Cumhuriyeti Tarihi; Ottoman Society; Osmanlı Toplumu; Ataturk's Principles History of Revolution; Atatürk İlkeleri İnkılap Tarihi; Late Modern Ottoman History; Yakınçağ Osmanlı Tarihi; Ottoman history; Osmanlı Tarihi